High postoperative fertility rate following surgical management of colorectal endometriosis. Issue 9 (25th July 2018) - Roman, Horace; Chanavaz-Lacheray, Isabella; Ballester, Marcos; Bendifallah, Sofiane; Touleimat, Salma; Tuech, Jean-Jacques; Farella, Marilena; Merlot, Benjamin
Abstract: STUDY QUESTION: What are fertility outcomes in patients surgically managed for large deep endometriosis infiltrating the rectum who intend to get pregnant postoperatively? SUMMARY ANSWER: Surgical management for rectal endometriosis is followed by high pregnancy rates, with a majority of natural conceptions. WHAT IS KNOWN ALREADY: Optimal management such as surgery versus first-line ART for patients with severe deep endometriosis who desire pregnancy is not defined. STUDY DESIGN, SIZE, DURATION: The study included the patients enrolled in ENDORE randomized trial who attempted pregnancy after the surgery. From March 2011 to August 2013, we performed a two-arm randomized trial, enrolling 60 patients with deep endometriosis infiltrating the rectum up to 15 cm from the anus, measuring more than 20 mm in length, involving at least the muscular layer in depth, and up to 50% of rectal circumference. Postoperative follow-up was prolonged in 55 patients recruited at Rouen University Hospital, and varied from 50 to 79 months. No women were lost to follow-up. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients had either conservative surgery by shaving or disc excision, or radical rectal surgery by segmental resection. One gynecologist experienced in deep endometriosis surgery performed all the procedures, assisted when required by three general surgeons experienced in colorectal surgery. Institutional review board approval was obtained to extend postoperative follow-up to 10 years after the surgery. Among patients enrolled at Rouen University Hospital, women who intended to get pregnant after surgery were selected and followed up postoperatively every 6 months for 2 years, then every year. Pregnancy intention, fertility outcomes, conception mode, endometriosis recurrences and digestive and urinary outcomes were rigorously recorded. The primary outcome was postoperative pregnancy rate. Secondary outcomes were conception mode, the delay to conception from the day of surgery and the day when hormonal treatment was stopped, and delivery rate. Kaplan Meier curves were used to estimate the probability of conception after surgery. MAIN RESULTS AND THE ROLE OF CHANCE: Among the 55 patients enrolled at Rouen University Hospital, 25 had conservative and 30 had radical surgery, and their postoperative follow-up varied from 50 to 79 months. No patient was lost to follow-up. Among the 55 patients, 36 intended to get pregnant after surgery, 23 of whom had unsuccessfully attempted to conceive for more than 12 months before surgery (63%). At the end of follow-up, 29 patients achieved pregnancy (81%), and natural conception was recorded in 17 of them (59% of conceptions). As several women had more than 1 pregnancy (range: 0–3), we recorded 37 pregnancies, 24 natural conceptions (65%) and 29 deliveries (78%). The probabilities of achieving pregnancy at 12, 24, 36 and 48 months postoperatively were 33.4% (95% CI: 20.6–51.3%), 60.6% (44.8–76.8%), 77% (61.5–89.6%) and 86.8% (72.8–95.8%), respectively. Women who had been advised to attempt natural conception achieved pregnancy significantly earlier than patients referred for ART ( P = 0.008). In infertile patients, the postoperative pregnancy rate was 74%, and 53% of conceptions were natural. LIMITATIONS, REASONS FOR CAUTION: The main outcomes of the original trial were related to digestive function and not to fertility. Several factors impacting fertility could not be revealed due to small sample size. The study included a high percentage of young women with an overall satisfactory prognosis for fertility, as patients' median age was 28 years. The inclusion of only large infiltrations of the rectum does not allow the extrapolation of conclusions to small nodules of <2 cm in length. Only one skilled gynecologic surgeon performed all the procedures. WIDER IMPLICATIONS OF THE FINDINGS: First-line surgery can be considered in patients with deep endometriosis infiltrating the rectum and pregnancy intention. Patients receiving advice from experienced surgeons on conception modes were more likely to conceive faster after surgery. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a grant from the clinical research program for hospitals (PHRC) in France. The authors declare no competing interests related to this study. TRIAL REGISTRATION NUMBER: The original randomized trial is registered with ClinicalTrials.gov (number NCT 01291576).